Spatiotemporally consistent genomic signatures of reproductive isolation in a moving hybrid zone - Taylor, Scott A. (2014)
Studies of hybrid zone dynamics often investigate a single sampling period and draw conclusions from that temporal snapshot. Stochasticity can, however, result in loci with spurious outlier patterns, which is exacerbated by limited temporal or geographic sampling. Comparing admixed populations from different geographic regions is one way to detect repeatedly divergent genomic regions potentially involved in reproductive isolation. Temporal comparisons also allow us to control partially for the role of stochasticity, but the power of temporal sampling has not yet been adequately explored. In North America, black-capped (Poecile atricapillus) and Carolina (P. carolinensis) chickadees hybridize in a contact zone extending from New Jersey to Kansas. The hybrid zone is likely maintained by strong intrinsic selection against hybrids, and it is moving north. We used a reduced representation genomic approach and temporally spaced sampling-two samples of ∼80 individuals separated by a decade-to determine the pattern and consistency of selection and genomic introgression in the chickadee hybrid zone. We report consistently low introgression for highly divergent loci between P. atricapillus and P. carolinensis in this moving hybrid zone. This is strong evidence that these loci may be linked to genomic regions involved in reproductive isolation between chickadees.